Orthopaedic Injury Profiles in Methamphetamine Users: A Retrospective Observational Study. Issue 1 (1st January 2020) - Trasolini, Nicholas; Kang, Hyunwoo; Carney, John; Rounds, Alexis; Murrietta, Adam; Marecek, Geoffrey S.
Abstract : Introduction: We sought to characterize the prevalence of methamphetamine (MA) abuse and associated orthopaedic injury patterns at our level 1 trauma center. Methods: We conducted a retrospective review of all orthopaedic consults for the year 2016. Patients were classified as MA users based on urine toxicology results and social history. Results: The prevalence of MA use was 10.0%. MA users were more likely to present with hand lacerations and other infections ( P < 0.05 for all). Regarding the mechanism of injury, MA users were more likely to be involved in automobile versus pedestrian, automobile versus bicycle, ballistic, knife, closed fist, other assault/altercation, and animal bite injuries ( P < 0.05 for all). Discussion: MA use is prevalent at our level 1 trauma center. The prevalence and injury patterns of MA abuse warrant deeper study into the effects of this drug on orthopaedic outcomes. Level of Evidence: Level III